Associations of sport participation, muscle-strengthening exercise and active commuting with self-reported physical fitness in school-aged children - Shi, Chongyan; Chen, Sitong; Wang, Lei; Yan, Jin; Liang, Kaixin; Hong, Jintao; Shen, Hejun (Frontiers in Public Health, 2022)
Evidence has numerously suggested the positive association between physical activity and physical fitness in schoolchildren. However, little is known about some neglected modalities of physical activity and their associations with physical fitness. Owing to the COVID-19 pandemic, it is unlikely to conduct a field-based assessment of physical fitness, which needs a workable assessment of physical fitness. Hence, this study aimed to explore the associations of sports participation, muscle-strengthening exercise, and active school travel with self-reported physical fitness assessed by the International Fitness Scale (IFIS). 3807 study participants from 12 public schools in South-eastern China were recruited and 2407 of them provided valid data on variables that this study needed for analysis. Study participants were asked to self-report their sociodemographic factors (e.g., sex, grade, age), sports participation, muscle-strengthening exercise and active school travel. Generalized linear models were used to explore the associations of sports participation, muscle-strengthening exercise, and active school travel with self-reported physical fitness (comprising general physical fitness, cardiorespiratory fitness, muscular strength, speed and agility, and flexibility). 2407 children and adolescents with a mean age of 13.82 years were included in the final study analysis. There was no significant association between active school travel and physical fitness. In terms of sports participation and muscle-strengthening exercise, positively significant associations were found, which showed that a higher frequency of sports participation and more participation in muscle-strengthening exercise was associated with better performance of physical fitness. The current study offered evidence on the roles of some modalities of physical activity in physical fitness. To promote health in children and adolescents, encouraging them to engage in more sports participation and muscle-strengthening exercise is a good option.